Characterization and In Situ Carbon Metabolism of Phototrophic Consortia - Glaeser, Jens (American Society for Microbiology, 2003)
A dense population of the phototrophic consortium “Pelochromatium roseum” was investigated in the chemocline of a temperate holomictic lake (Lake Dagow, Brandenburg, Germany). Fluorescence in situ hybridization revealed that the brown epibionts of “P. roseum” constituted up to 37% of the total bacterial cell number and up to 88% of all green sulfur bacteria present in the chemocline. Specific amplification of 16S rRNA gene fragments of green sulfur bacteria and denaturing gradient gel electrophoresis fingerprinting yielded a maximum of four different DNA bands depending on the year of study, indicating that the diversity of green sulfur bacteria was low. The 465-bp 16S rRNA gene sequence of the epibiont of “P. roseum” was obtained after sorting of individual consortia by micromanipulation, followed by a highly sensitive PCR. The sequence obtained represents a new phylotype within the radiation of green sulfur bacteria. Maximum light-dependent H(14)CO(3)(−) fixation in the chemocline in the presence of 3-(3,4-dichlorophenyl)-1,1-dimethylurea suggested that there was anaerobic autotrophic growth of the green sulfur bacteria. The metabolism of the epibionts was further studied by determining stable carbon isotope ratios (δ(13)C) of their specific biomarkers. Analysis of photosynthetic pigments by high-performance liquid chromatography revealed the presence of high concentrations of bacteriochlorophyll (BChl) e and smaller amounts of BChl a and d and chlorophyll a in the chemocline. Unexpectedly, isorenieratene and β-isorenieratene, carotenoids typical of other brown members of the green sulfur bacteria, were absent. Instead, four different esterifying alcohols of BChl e were isolated as biomarkers of green sulfur bacterial epibionts, and their δ(13)C values were determined. Farnesol, tetradecanol, hexadecanol, and hexadecenol all were significantly enriched in (13)C compared to bulk dissolved and particulate organic carbon and compared to the biomarkers of purple sulfur bacteria. The difference between the δ(13)C values of farnesol, the major esterifying alcohol of BChl e, and CO(2) was −7.1%, which provides clear evidence that the mode of growth of the green sulfur bacterial epibionts of “P. roseum” in situ is photoautotrophic.